Control interno operativo financiero y su efecto en la rentabilidad de la compañía Consmariscal constructora mariscal & mariscal S. A. periodo 2019 - Cunalata Guato, Daisy Mirella (2021)
The main objective of the research related to internal financial operational control is to evaluate the internal financial operational control and its effect on the profitability of the company Consmariscal Constructora Mariscal & Mariscal S.A. period 2019. To develop the research it was necessary to review concepts and theories extracted from books and web pages that are related to the proposed topic; the continuity of the development of this thesis demanded the application of a research methodology including descriptive, deductive, inductive and statistical, among others, in addition to these it was necessary to obtain information from primary source to which an interview and survey was applied in order to determine the state of internal control; following this is presented the results obtained for the evaluation of internal control this evaluation was carried out through the implementation of the COSO I Report 2013 and its five components resulting in a high level of confidence in the established controls of 83% and a low risk level of 17% however despite this result, fallacy could be identified as an unremeaned internal regulation since 2016 , audit not contracted therefore internal control has not been evaluated, payments to suppliers most of them do not have the firms of responsibility and approval among other losses detected; despite these fallacys the company has been able to obtain a return of 38% this because its investments have been recovered in the shortest possible time and the costs and expenses of the entity have been adequately managed. Keyword: Financial operation, internal control, profitability